Prevalence of smoking and its associated factors with smoking among elderly smokers in Malaysia: findings from a nationwide population-based study. Issue 1 (December 2016) - Lim, K.; Jasvindar, K.; Cheong, S.; Ho, B.; Lim, H.; Teh, C.; Lau, K.; Suthahar, A.; Ambigga, D.
Abstract Background The determination of smoking prevalence and its associated factors among the elderly could provide evidence-based findings to guide the planning and implementation of policy in order to will help in reducing the morbidity and mortality of smoking-related diseases, thus increase their quality of life. This paper describes the rate of smoking and identifies the factor(s) associated with smoking among the elderly in Malaysia. Methods A representative sample of 2674 respondents was obtained via a two-stage sampling method in proportion to population size. Face-to-face interviews were conducted using a set of standardized validated questionnaire. Data was weighted by taking into consideration the complex sampling design and non-response rate prior to data analysis. Univariable and multivariable logistic regression were used to determine the factor/s associated with smoking. Results The prevalence of non-smokers, ex-smokers and current smokers among Malaysians aged 60 years and above were 36.3 % (95 % CI = 32.7–39.8), 24.4 % (95 % CI = 21.2–27.5) and 11.9 % (95 % CI = 9.5–14.3), respectively. Current smokers were significantly more prevalent in men (28.1 %) than in women (2.9 %), but the prevalence declined with advancing age, higher educational attainment, and among respondents with known diabetes, hypertension and hypercholesterolemia. Multivariable analysis revealed that males (aOR, 18.6, 95 % CI 10.9-31.9) and other Bumiputras (aOR 2.58, 95 % CI 1.29-5.15) were more likely to smoke. in addition, elderly with lower educational attainment (aOR, 1.70, 95 % CI 1.24-7.41) and those without/unknown hypertension also reported higher likelihood to be current smokers (aOR 1.98, 95 % CI 1.35-2.83). However, there were no significant associations between respondents with no/unknown diabetes or hypercholesterolemia with smoking. Conclusions In short, smoking is common among elderly men in Malaysia. Therefore, intervention programs should integrate the present findings to reduce the smoking rate and increase the smoking cessation rate among the elderly in Malaysia and subsequently to reduce the burden of smoking-related disease.